Polymerizations Mediated by Well-Defined Rhodium Complexes - Tan, Nicholas Sheng Loong; Lowe, Andrew (WILEY-V C H VERLAG GMBH, 2020)
This Minireview details the current state-of-the-art relating to (co)polymerizations mediated by well-defined RhI -ethynyl, vinyl, and aryl complexes. In particular, we focus on RhI species suitable for the (co)polymerization of phenylacetylenes, arylisocyanides, as well as propargyl esters and amides.